PEMBUATAN DAN PEMANFAATAN ARANG AKTIF DARI AMPAS DAUN TEH - R Sudradjat; Ani Suryani Suryani (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
This report deals with an experiment on the manufacture of activated charcoal from the wastes of tea leaf processing. The purpose of the experiment was firstly, to evaluate the influence of H3P04 concentration as a chemical activator on the yield of activated charcoal and its quality, and secondly, to assess the possible use o( the corresponding activated charcoal in purifying fructose syrup as well as alcoholic spirit, and reducing the Fe1 ions in the pond water . The tealeaf wastes were at first immersed in H1P04 solutions at four different concentrations (i.e. 5, 10, 15 and 20 %).for 24 hours. The wastes were removed and airdried. The activated charcoal was produced by pyrolyzing the airdry tealeaf wastes in an electrical heated retort at 850°C, followed by the activation process. The steam was introduced into the retort and passed through the pyrolized tealeaf wastes for 120 minutes.. The result revealed that the best quality ofthe activated charcoal was obtained with H3P04 immersion at 10 % with the yield of activated charcoal 13.78 %; the moisture content 6.92 %; ash content 15.68 %, volatile matter 4.68 % and fixed carbon 72. 71 %. Adsorptive capacity of iodine was 796.82 mglg, benzene 5.58 %, CHC1,4.14 % and adsorptive capacity of CC14,14.19 %.The quality of fructose syrup and alcoholic spirit after both being purified with the activated charcoal apparently improved. This was shown by the increases in clarity from 87.0 % to 92.0 97.2 % (for fructose syrup) and from 243.0 mg/L to 255.6278.4 mg/L (for alcoholic spirit). The quality of the deepweel water or particularly pond water also after being treated with the activated charcoal improved as well with the decrease in Fe3+ ions from 0.079 % to 0.016 0.045 %. The production cost to manufacture activated charcoal from tealeaf wastes was Rp 5,738.82/kg.